Effect of Water Retainer® During Seedling Period on Bioactive Components of Tomato (Solanum lycopersicum) - Rita Adél Tömösközi-Farkas; Ágnes Molnár-Mondovics; Barbara Ildikó Schmidtné Szantner (Agronomy)
As a result of climate change, drought and the unequal distribution of rainfall is a worldwide problem. Drought stress on plants affects not only the yield, but also the amount and ratio of bioactive components in tomato fruit. The aim of the present work was to investigate the effect of a new soil biodegradable water-retention agent (Water and Soil’s Water Retainer®, Water and Soil Ltd., Budapest, Hungary) containing natural ingredients during the seedling period and under different irrigation conditions on the product volume, dry matter content and on some characteristic secondary metabolites in tomato fruits. The study was conducted to screen four different irrigation and soil treatment combination treatments for production and quality characteristics (polyphenols, tocopherols, carotenoids, vitamin C) to check the effect of seedling-stage stress on the tomato yield and bioactive components. Significant differences were found among the treatment and the cultivation seasons for the phytochemical content of fruits. The average yield and BRIX value did not change as a result of the Water Retainer® compared to the irrigated samples, but the amount of lycopene, Vitamin C, antioxidant capacity, and total polyphenol content increased significantly with the use of the Water Retainer®. In the two cultivation seasons, the highest concentration of lycopene and Vitamin C (114.30 ± 3.18 μg.g−1 and 338.10 ± 13.70 μg.g−1 fwt, respectively) was determined in fruits of 50% irrigation + 1.5 mL/m2 WR®-treated plants. The highest measured antioxidant capacity and total polyphenol content were 21.54 ± 0.17 mMTr/kg and 504 ± 44 mg GAE/kg, respectively, in the same treated samples. We found that seedlings exposed to drought stress, and after planting, when grown under ideal conditions in the field, can be distinguished from each other, despite the fact that there was only a difference between their cultivation during the seedling period. This may prove that rehydration is not sufficient to completely restore the metabolomic processes of stressed plants.